Sulphide-enhanced hydrolysis of primary sewage sludge : implications for the bioremediation of sulphate-enriched wastewaters - Whittington-Jones, Kevin John (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2000)
The potential application of sulphate reducing bacteria for the bioremediation of acid mine drainage has already been recognised, and offers significant financial advantages over conventional chemical treatment approaches. Although the technology has been demonstrated successfully on both small- and large-scale, it's extensive implementation has been constrained by the provision of suitable and cost effective electron donor and carbon sources. Primary sewage sludge is readily available in large quantities, but the slow rate of solubilization and low yield of soluble products do not apparently favour its use for this application. A number of pre-treatment steps have been introduced in an attempt to improve the yield and rates under methanogenic conditions. However, although early work suggested that degradation of lignocellulose and proteins may be more rapid under sulphate reducing conditions, the fate of primary sewage sludge under these conditions has been ignored. It was proposed that by combining the hydrolysis of primary sewage sludge and biological sulphate reduction, in a settling sludge bed, both processes would be enhanced. The aim of this study was to test this hypothesis on laboratory- and pilot-scale, and attempt to elucidate the underlying mechanism involved. The solubilization of primary sewage sludge was enhanced in the presence of sulphate reduction in continuous laboratory-scale reactors. Particulate matter accumulated in the bed of non-sulphidogenic systems, but not in sulphidogenic ones. This was attributed to increased solubilization and the smaller average floc size in the latter. Solubilization occurred within the settling sludge bed of the reactors, and offered a possible explanation for the better performance of the multiple- over single-stage reactor. A pilot-scale Falling Sludge Bed Reactor was constructed at Grootvlei Gold Mine, Springs, South Africa, and resulted in the solubilization of more than 70% of the influent primary sewage sludge. The system was also found to be highly resilient to severe perturbations, and returned rapidly to steady-state. Flask studies revealed that the hydrolysis of both proteins and complex carbohydrates was accelerated in the presence of biological sulphate reduction or sulphide. A study of the enzymology of sludge digestion revealed that sulphate reduction had little direct effect on the activity of the hydrolytic enzymes, but that reactor design was critical in the prevention of washout of these enzymes. Finally, a descriptive model was developed to explain the enhanced hydrolysis of primary sewage sludge. The model incorporated the effect of sulphidogenesis on floc fracture and reflocculation, and likely implications for mass transfer limitations.
Keywords: Bioremediation; Sewage sludge; Hydrolysis